Optimisme Disposisional dan Pengukurannya pada Orang Usia Lanjut - Indra Yohanes Kiling; Yunita Marcelini Manafe; Beatriks Novianti Bunga (Universitas Nusa Cendana, 2019)
The elderly as a vulnerable group of people in the community has various physical, psychological and social adversities in their life. In this age, someone who is of old age should have a positive attribute that could help the person to achieve a life with quality. Dispositional optimism is an individual’s positive attribute that could give a positive impact to elderly people. This paper reviewed theories related to dispositional optimism by reviewing existing literature. Indicators and measurement of dispositional optimism also discussed in this paper. Dispositional optimism theory was reviewed from the perspective of the initial founder of the theory and then further looked at its development in global application. Indicators of dispositional optimism were discussed to further understand the process of measurement of the concept itself. The measurement of dispositional optimism was often referred to as the Life Orientation Test scale, which was developed into various kinds of similar tests in order to use the test in other settings. The discussion in this paper hopefully could provide knowledge regarding dispositional optimism in elderly people especially future research in an Indonesian setting.